The 7th habits of highly effective people : powerful lessons in personal change - Covey, Stephen R. (New york : Pocket books, 2004)
A leading management consultant outlines seven organizational rules for improving effectiveness and increasing productivity at work and at home
Includes bibliographical references and index.
Keywords: Success -- Psychological aspects; achievement; Character; Achievement